Pengaruh Kombinasi Fly Ash Dan Bottom Ash Sebagai Bahan Substitusi Pada Campuran Beton Terhadap Sifat Mekanis - Tengku Tantoni Yahya; Alex Kurniawandy; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Fly ash and bottom ash were waste that generated from the power plant burning coal process. Fly ash and bottom ash has the potential to be developed as a basic ingredient in concrete composites. This research aimed to obtain the properties of fresh concrete and hard concrete of the combined effect of fly ash and bottom ash as a substitute ingredient in composite concrete. This research has examined the influence of a combination of waste fly ash and bottom ash to the compressive strength of absorption, porosity, permeability, shrinkage of concrete, setting time of cement. The percentage of fly ash waste and bottom ash waste that used were 15% by weight of cement and 15% of the weight of the sand. Research results show that using of 15% fly ash and 15% bottom ash was tending to decrease the compressive strength of concrete. However, the compressive strength was generated still whitin the standard of concrete strength design. Applicaton of 15% fly ash and 15% bottom ash were experiences to increase the value of absorption, permeability and concrete porosity, but reduce the concrete shrinkage. Meanwhile, setting time of 15% fly ash and 15% bottom ash were faster than without any composite.Keywords : concrete, fly ash, bottom ash, permeability, shrinkage, setting time.